Patient Anxiety and Depression Moderate the Effects of Increased Self-management Knowledge on Physical Activity: A Secondary Analysis of a Randomised Controlled Trial on Health-Mentoring in COPD. (3rd September 2015) - Schüz, Natalie; Walters, Julia A.E.; Cameron-Tucker, Helen; Scott, Jenn; Wood-Baker, Richard; Walters, E. Haydn
Abstract: Objective . Anxiety and depression are common comorbidities in people with chronic obstructive pulmonary disease (COPD). While these comorbidities could potentially lead to a higher motivation to learn about self-management, they could also inhibit patients from translating this knowledge into appropriate self-management behaviours. This paper explores the moderating effects of anxiety and depression on a health-mentoring intervention, focusing on mechanisms of change (mediation). Methods . 182 COPD patients participated in an RCT, with anxiety and depression assessed by the Hospital Anxiety and Depression Scale (HADS), self-management knowledge by the Partners in Health Scale, and spontaneous physical activity using accelerometers, all measured at baseline, 6 and 12 months. The moderated mediation model tested the intervention's effect on physical activity, mediated via changes in self-management knowledge, at different levels of anxiety and depression. Results . Knowledge mediated the effect of the intervention on changes in physical activity only for participants reporting low levels of anxiety or depression. Both acted as moderators: Increased knowledge led to more physical activity among participants reporting low anxiety or depression and to less activity among highly anxious or depressed participants. Conclusion . Although health-mentoring interventions can be an effective tool to increase knowledge and physical activity among COPD patients, it is essential to take anxiety and depression into account, as increased knowledge may have detrimental effects in highly anxious or depressed participants. This suggests that patients with elevated anxiety or depression may need to be treated appropriately before engaging in chronic disease self-management interventions.